A novel hybrid FS‐FEM/SEA for the analysis of vibro‐acoustic problems. (26th March 2015) - Wu, F.; Liu, G. R.; Li, G. Y.; Cheng, A. G.; He, Z. C.; Hu, Z. H.
Summary Predicting the frequency response of a complex vibro‐acoustic system becomes extremely difficult in the mid‐frequency regime. In this work, a novel hybrid face‐based smoothed finite element method/statistical energy analysis (FS‐FEM/SEA) method is proposed, aiming to further improve the accuracy of 'mid‐frequency' predictions. According to this approach, the whole vibro‐acoustic system is divided into a combination of a plate subsystem with statistical behaviour and an acoustic cavity subsystem with deterministic behaviour. The plate subsystem is treated using the recently developed FS‐FEM, and the cavity subsystem is dealt with using the SEA. These two different types of subsystems can be coupled and interacted through the so‐called diffuse field reciprocity relation. The ensemble average response of the system is calculated, and the uncertainty is confined and treated in the SEA subsystems. The use of FS‐FEM 'softens' the well‐known 'overly stiff' behaviour in the standard FEM and reduces the inherent numerical dispersion error. The proposed FS‐FEM/SEA approach is verified and its features are examined by various numerical examples. Copyright © 2015 John Wiley & Sons, Ltd.